2014
DOI: 10.1063/1.4886971
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced spin transition revealed by iron M2,3-edge spectroscopy

Abstract: We present a method to characterize pressure induced magnetic high to low spin transition in iron sulphide using x-ray Raman scattering spectroscopy at the iron M2,3-edge. The advantage of this method is that the observed spectral changes between pressures of 1.7 GPa and 10.1 GPa can be used with the help of atomic multiplet calculations to determine the crystal field splitting parameters associated with the spin transition. We discuss the potential of this M2,3-edge spectroscopy to investigate the irons elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…As the scattering vector becomes larger, the octupole transition become dominant and the dipole transition becomes subordinate; the intensity around the transferred energy 53 ∼ 55 eV become intense and the intensity above 55 eV becomes weak. A similar tendency can be seen in the XRS spectra on iron oxides 10. In order to compare the observation and the calculation, we naively assume that the lifetime broadening is Γ = max (0.1E + 0.14, 0.14) eV, where E is the relative transferred…”
mentioning
confidence: 66%
“…As the scattering vector becomes larger, the octupole transition become dominant and the dipole transition becomes subordinate; the intensity around the transferred energy 53 ∼ 55 eV become intense and the intensity above 55 eV becomes weak. A similar tendency can be seen in the XRS spectra on iron oxides 10. In order to compare the observation and the calculation, we naively assume that the lifetime broadening is Γ = max (0.1E + 0.14, 0.14) eV, where E is the relative transferred…”
mentioning
confidence: 66%
“…As shown by Nyrow et al . 40 the spin transition pressure and spin transition range can be characterized by the integral of the absolute value of A ( p ), which is given by the differences between spectra measured at certain pressure p and a HS reference measured at ambient conditions or low pressure. As our siderite reference, here we use the M 2,3 -edge and L 2,3 -edge measured at ambient conditions and 2.4 GPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we exploit x-ray Raman scattering (XRS) spectroscopy to study the iron M 2,3 -edges 40 and L 2,3 -edges 41 of siderite and magnesiosiderite in situ at high pressure in a diamond anvil cell (DAC) in order to probe the electronic structure of iron. XAS measurements at the iron L 2,3 -edges (2p→3d) for light- or temperature induced spin transitions have shown that the L 2,3 -edge is highly sensitive to the spin state 42 , 43 , but high pressure experiments using DAC prevent the use of soft x-ray absorption for the in situ study of the L 2,3 - and/or M 2,3 -edges of iron in the carbonates due to the strong absorption of soft x-rays by the diamond anvils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][41][42][43] Recently, in situ high pressure measurements of the Fe M 2/3 -edge demonstrated the ability to track the pressure induced spin cross-over in FeS and to extract quantitative information about the crystal eld splitting of the 3d states in iron. 44 The Fe M 2/3 -edge is signicantly modied by weak changes of the oxidation and spin state, but it is less sensitive to the local coordination. 45 Recently, magnetic circular dichroism of X-ray Raman scattering was observed at the iron L 2/3 -edge of pure iron.…”
Section: Introductionmentioning
confidence: 99%